Implementasi Program Enterprise Resource Planning IPOS 4.0 pada Majujaya Furniture (PT. Asia Oriental Kreasindo) - Michael Sutanto; Jullend Gatc (UNIVERSITAS KALBIS, 2022)
Majujaya Furniture is a company that still uses manual business process recording techniques. Starting from sales, purchases, to inventories, they still use the traditional method, which is recorded using manual invoice and receipt. This has led to many problems such as the difficulty of finding inventory data which still available and also the inaccuracy of the data due to too many invoices and receipts are made. Therefore, an Enterprise Resource Planning (ERP) system for sales, purchases, and inventory of goods is very suitable to solve these problems. The stages of implementing this ERP begin with interviews and observation, identifying the business processes in the company, select the ERP application, configure the ERP application module, and finally carry out the implementation and testing. The results of this study indicate that the ERP software that has been selected and implemented, IPOS 4.0 can solve problems in Majujaya Furniture.